Race science without racists: how bigoted paradigms persist in allergy research - Myles, Ian A. (Frontiers in Public Health, 2024)
In the wake of the murder of George Floyd and the massacre in Buffalo, the editorial boards of the prominent scientific publication companies formally apologized for their journals’ historical role in advancing race science and promised to improve their standards. However, flowery commentaries cannot undo the consistent pattern of endorsing biologic differences between ethnic groups, even when discussing diseases or traits that are not considered politically charged. In this report, an exemplar is made of a recent publication claiming to identify phenotypes of atopic dermatitis that are distinct between European Americans, Asians, and African Americans. The insufficiency of the evidence and logic underlying these claims are discussed. Although devoid of malice, numerous publications continue to demonstrate how claims of biological differences between races is mainstreamed in modern scientific publications. Overall, the goal of this work is to challenge the scientific community, particularly the publication companies, to evaluate how assumptions of innate biologic disadvantage have clouded assessments of racial disparities in disease beyond the topics that are more stereotypical of race science.